2023
DOI: 10.1038/s41467-023-36441-z
|View full text |Cite
|
Sign up to set email alerts
|

Structural basis for membrane attack complex inhibition by CD59

Abstract: CD59 is an abundant immuno-regulatory receptor that protects human cells from damage during complement activation. Here we show how the receptor binds complement proteins C8 and C9 at the membrane to prevent insertion and polymerization of membrane attack complex (MAC) pores. We present cryo-electron microscopy structures of two inhibited MAC precursors known as C5b8 and C5b9. We discover that in both complexes, CD59 binds the pore-forming β-hairpins of C8 to form an intermolecular β-sheet that prevents membra… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
21
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 20 publications
(21 citation statements)
references
References 92 publications
0
21
0
Order By: Relevance
“…This cleaves complement factor C5, generating C5b, which recruits factors C6 and C7 to cause membrane association. Factors C8 and C9 can then bind to C5b7 on the pathogen surface, leading to the formation of a pore which mediates cell death ( Couves et al, 2023 ).…”
Section: Introductionmentioning
confidence: 99%
“…This cleaves complement factor C5, generating C5b, which recruits factors C6 and C7 to cause membrane association. Factors C8 and C9 can then bind to C5b7 on the pathogen surface, leading to the formation of a pore which mediates cell death ( Couves et al, 2023 ).…”
Section: Introductionmentioning
confidence: 99%
“…Although these bacterial toxins can still bind cholesterol-rich membranes, CD59 determines the species specificity for these virulence factors [ 9 ] and coordinates oligomerization necessary for structural transitions en route to the final pore [ 12 ]. While there is extensive structural information on how CD59 engages MAC proteins [ 13 ] and CDCs [ 14 , 15 ], investigating the molecular interactions of GPI-anchored CD59 in a membrane environment will inform how CD59 satisfies its opposing roles in pore formation.…”
Section: Introductionmentioning
confidence: 99%
“…CD59 blocks MAC at the first instance of membrane perforation by binding C8α [ 4 , 27 ]. Recent cryo-electron microscopy (cryoEM) studies have shown how CD59 re-directs pore-forming residues of the C8α MACPF [ 13 ]. CD59 binds C8α through a C-terminal β-strand of its central β-sheet, catching the cascading transmembrane residues and templating the newly formed C8α β-hairpin.…”
Section: Introductionmentioning
confidence: 99%
“…This cleaves complement factor C5, generating C5b, which recruits factors C6 and C7 to cause membrane association. Factors C8 and C9 can then bind to C5b7 on the pathogen surface, leading to the formation of a pore which mediates cell death 18 .…”
Section: Introductionmentioning
confidence: 99%